2011
DOI: 10.1158/1078-0432.ccr-10-2619
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of mir-203 in Prostate Cancer Progression and Metastasis

Abstract: Purpose: Advanced metastatic prostate cancer (PCa) is a fatal disease, with only palliative therapeutic options. Though almost 80% of cases of metastatic PCa present bone metastasis, our current understanding of the molecular mechanisms that govern this metastatic dissemination remains fragmentary. The main objective of the present study was to identify microRNA (miRNA) genes that regulate metastatic PCa.Experimental Design: miRNA expression profiling was done in human prostate cell lines to identify dysregula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
225
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(243 citation statements)
references
References 41 publications
14
225
2
2
Order By: Relevance
“…[30] In a study where miR-203 (new nomenclature: miR-203a) expressions in malign, and normal prostate tissue were compared, decrease in miR-203 expression was demonstrated in correlation with advanced PCa, and its"anti-metastatic" value was suggested. [35] Also in our study, in compliance with the literature decrease in miR-203 levels was observed.…”
Section: Discussionsupporting
confidence: 92%
“…[30] In a study where miR-203 (new nomenclature: miR-203a) expressions in malign, and normal prostate tissue were compared, decrease in miR-203 expression was demonstrated in correlation with advanced PCa, and its"anti-metastatic" value was suggested. [35] Also in our study, in compliance with the literature decrease in miR-203 levels was observed.…”
Section: Discussionsupporting
confidence: 92%
“…Zhang et al 47 observed that miR-17-3p regulates the expression of vimentin and altered expression of miR-17-3p decreases the tumorigenic behavior and reduces tumor size in nude mice. Saini et al 51 also noted that relative miR-203 expression is lower in prostate cancer cell lines derived from bone metastasis, and over-expression of miR-203 has a negative effect on the development of metastases in nude mice. Significantly, miR-203 has been shown to repress bone-specific transcriptional regulators, such as Runx2 and Dlx5, in addition to regulating pro-metastatic genes ZEB2, Bmi and Survivin.…”
Section: Mirnas As Biomarkers In Prostate Cancer Pathogenesismentioning
confidence: 98%
“…47 Apoptosis is also controlled by molecules not belonging to the BCL2 family. For example, the inhibitor of apoptosis protein (IAP), survivin, is overexpressed in HCC and is controlled by miR-203, 48 a miRNA silenced by aberrant DNA methylation in HCC tissue. 23 Another miRNA, miR-21, appears to promote cell survival under stressful conditions.…”
Section: 3mentioning
confidence: 99%